Application of carbon materials, biochar and preparation method and application thereof

Through pre-carbonization and gas-phase deaeration treatment of low-sulfur content biomass carbon, carbon materials with high fixed carbon content were prepared, which solved the problems of insufficient feed stability and battery material performance in biomass gasification technology, and achieved high efficiency, Low-cost battery material preparation and biomass resource utilization.

CN117728001BActive Publication Date: 2025-01-07JINAN SHENGQUAN GRP SHARE HLDG CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311196036.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-09-16
Filing Date
2023-09-15
Publication Date
2025-01-07
Estimated Expiration
2043-09-15

AI Technical Summary

Technical Problem

The high-pressure feeding method in the existing biomass gasification technology is complicated to operate and poor stability, resulting in frequent shutdown of the gasifier and reduced syngas content and system efficiency; at the same time, graphite has low specific capacity and low temperature performance in lithium-ion batteries. Poor and lithium dendrites are prone to occur on the surface of the negative electrode, and the cycle performance and primary efficiency of hard carbon as the negative electrode material of sodium ion battery are insufficient.

Method used

Using biomass carbon with low sulfur content and no volatile organic compounds, high fixed carbon content and low ash carbon materials are prepared through pre-carbonization, gas-phase deaeration and calcination treatment, and is used to prepare battery hard carbon materials, especially sodium Ion battery hard carbon anode material. The method includes concentrating, carbonizing and washing the cooking liquid, controlling the carbonization temperature and time to reduce energy consumption, and improving the fixed carbon content and cycling stability of the material.

Benefits of technology

It realizes efficient preparation of biomass carbon, reduces production costs, improves the charging and discharge efficiency and cycle stability of battery materials, increases the application scope of biomass resources, and solves the feed stability and Problems with battery material performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004452713410000191
    Figure BDA0004452713410000191
  • Figure BDA0004452713410000281
    Figure BDA0004452713410000281
  • Figure HDA0004452713470000011
    Figure HDA0004452713470000011
Patent Text Reader

Abstract

The present application discloses an application of a carbon material in the preparation of a battery, wherein the carbon material is prepared from biochar. The present application also discloses a biochar prepared by the above method and the application of the biochar in fuel, gasification raw material for a gasifier, and carbon material for a battery. The biochar of the present application has moderate volatile matter content, low sulfur content, uniform particle size, high bulk density, low ash content, high calorific value, low production cost, and significant economic benefits. It is a clean and renewable biomass energy source. The biochar of the present application can be used in fuel, gasification raw material for a gasifier, carbon material for a battery, and soil conditioner.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of biomass refining and comprehensive utilization, and specifically relates to the application of a carbon material in the preparation of batteries, a biomass charcoal and its preparation method and application. Background Art

[0002] Due to the non-renewable nature of primary energy sources such as coal, oil and natural gas, as well as the greenhouse effect and environmental problems during their use, the clean and environmentally friendly utilization of renewable biomass resources that have both material and energy properties has shown great development potential and has become the focus of research and application.

[0003] my country produces 700 million tons of agricultural straw and 200 million tons of forestry solid waste annually, a considerable portion of which is discarded or burned on site, causing energy waste and environmental pollution. These agricultural and forestry resources biomass can be dried and crushed to produce synthesis gas with H2 and CO as the main components through gasification reaction, which is the main way to achieve clean and environmentally friendly utilization of biomass energy. The synthesis gas obtained after gasification can be purified and converted to synthesize clean fuels and high value-added chemicals through Fischer-Tropsch synthesis technology or other conversion technologies.

[0004] Similar to coal gasification technology, the current biomass gasification mainly uses firewood and straw as the main raw materials. After preliminary crushing to a suitable particle size range, it is transported to the gasifier in the form of block solids (particle size 8-50mm) or solid particles (particle size 4-8mm) through inert gas for gasification reaction.

[0005] High-pressure feeding is a prerequisite for realizing high-pressure gasification technology, which can significantly reduce the volume of the gasifier and the energy consumption of pressurizing the syngas in the downstream process section. For solid biomass gasification raw materials, the pressure of the gas transported in the feed lock hopper needs to be higher than the pressure of the gasifier to achieve high-pressure feeding. This feeding method is relatively cumbersome to operate and has poor stability. Since mechanical valves are used to seal high-pressure gas, long-term high-frequency switching operations are prone to valve failure or damage, causing the gasifier to be forced to shut down due to feed interruption. At the same time, the inert gas used for biomass material transportation is not easy to remove in the downstream process section, which will cause a decrease in the syngas content and system efficiency. On the other hand, the gasifier has high requirements for the stability of the raw materials. Even if the feed amount can be kept stable, changes in the type and composition of the feed biomass will also lead to significant fluctuations in the gasification conditions, gas production and syngas composition. However, the composition of biomass raw materials is complex and changes with type and season, which poses a challenge to the stable regulation of the gasifier working conditions and restricts the maturity and perfection of biomass dry material gasification technology. Therefore, high-pressure feeding of biomass raw materials and the stability of material composition have become important technical issues affecting its resource utilization. In addition, impurities in biomass are prone to scaling during the gasification process and the transportation of gasification products, causing equipment and pipeline blockage.

[0006] Due to the shortage of fossil resources, the development and application of carbon materials have been greatly restricted in recent years. Biomass resources such as forestry biomass and agricultural straw are renewable resources and have become substitutes for fossil resources. Most biomass resources are rich in carbon, so the preparation of various carbon materials using renewable biomass resources as raw materials has always attracted much attention.

[0007] There are many types of carbon materials for batteries, generally including soft carbon, hard carbon, graphite, etc., among which graphite is the most widely used in lithium-ion batteries. However, graphite anodes have problems in application, such as low specific capacity (theoretical specific capacity 372mAh / g), poor low-temperature performance, and easy generation of lithium dendrites on the surface of the anode. In addition, graphite needs to be processed by high-temperature graphitization, which consumes a lot of energy, hindering the development of related battery products.

[0008] Hard carbon refers to carbon that is difficult to graphitize and is a type of amorphous carbon material. Hard carbon has a very high reversible specific capacity for lithium, generally 500 to 1000 mAh / g. Hard carbon has attracted widespread attention due to its low cost, excellent cyclicity and suitability for discharge under high current.

[0009] Sodium-ion batteries are secondary batteries that use the process of sodium ions intercalating and deintercalating between the positive and negative electrodes to achieve charge and discharge. Compared with lithium-ion batteries, sodium-ion batteries have the following advantages: sodium salt raw materials are abundant and inexpensive; due to the characteristics of sodium salts, low-concentration electrolytes can be used to reduce costs; sodium ions do not form alloys with aluminum, and aluminum foil can be used as the negative electrode collector, further reducing costs and weight; due to the sodium-ion battery's no over-discharge characteristics, sodium-ion batteries are allowed to discharge to zero volts. Sodium-ion batteries have a high energy density and obvious cost advantages; however, due to the unsatisfactory electrochemical properties of electrode materials, the development of sodium-ion batteries has been relatively slow, and finding suitable electrode materials is one of the keys to the large-scale practical application of sodium-ion energy storage batteries.

[0010] The atomic radius of sodium ions is larger than that of lithium ions. Due to the small spacing between graphite layers (0.34nm), it is difficult for sodium ions to enter the graphite layer. As a negative electrode material for sodium ion batteries, hard carbon has many advantages over traditional electrode graphite. Hard carbon has a loose, porous and interlaced layered structure, which can store a large amount of sodium ions, but its initial efficiency as a sodium ion negative electrode material is relatively low, and its cycle performance is poor. As in the prior art, CN102701184A discloses a sodium ion battery carbon negative electrode material with a large interlayer spacing, which is obtained by pyrolysis of aromatic organic matter, and the pyrolysis conditions are carbonization at 600-1600°C in an inert atmosphere for 2-24h; the aromatic organic matter is polyphenyl, phenolic acid, furfural, polynaphthalene, polyanthracene, asphalt or their derivatives. By controlling the pyrolysis conditions, the pyrolytic carbon material has a certain carbon interlayer spacing and has good reversible sodium ion deintercalation performance. However, the reversible capacity of the negative electrode material is only 175-260 mAh / g, and its capacity and cycle performance cannot meet the use requirements. Summary of the invention

[0011] In order to solve the problems existing in the above-mentioned prior art, the purpose of the present application is to provide a biomass charcoal with low sulfur content, no volatile organic compounds (VOCs), uniform particle size, high bulk density, low ash content, high calorific value and low production cost, and a preparation method and application thereof, and also to provide an application of a carbon material made from the above-mentioned biomass charcoal in the preparation of batteries.

[0012] The specific technical solutions of this application are as follows:

[0013] 1. An application of a carbon material in preparing a battery, wherein the carbon material is made from biomass charcoal.

[0014] 2. The use according to item 1, wherein the carbon material is obtained by pre-carbonizing, gas phase deashing and calcining the biochar;

[0015] Preferably, the carbon material is a battery hard carbon material;

[0016] Preferably, the battery hard carbon material is a sodium ion battery hard carbon material;

[0017] Preferably, the battery hard carbon material is a battery hard carbon negative electrode material.

[0018] 3. The use according to item 1 or 2, wherein the biochar is prepared by the following method:

[0019] Concentrating the cooking liquid to obtain solids, wherein the solids contain lignin, inorganic salts, hemicellulose and cellulose;

[0020] The solid is carbonized, and optionally washed with a solvent and filtered after carbonization to obtain biochar.

[0021] 4. The use according to item 3, wherein the solvent is selected from any one or more of water, ethanol, methanol, acid solution, and alkaline solution;

[0022] Preferably, the washing temperature is 0 to 100° C., more preferably 60 to 80° C., and the washing time is 0.1 to 120 min, more preferably 30 to 60 min.

[0023] 5. The use according to item 3 or 4, wherein the concentration temperature is 30 to 220°C, preferably 50 to 200°C, and more preferably 70 to 140°C;

[0024] Preferably, the concentration time is 0.1 to 6 hours.

[0025] 6. The use according to any one of items 3 to 5, wherein, based on the total weight of the solids, the solids contain: 5 to 91 wt% of lignin, 1 to 10 wt% of inorganic salts, and 1 to 50 wt% of hemicellulose and cellulose.

[0026] 7. The use according to any one of items 3 to 6, wherein the carbonization temperature is 80 to 800° C., preferably 100 to 500° C.;

[0027] Preferably, the carbonization time is 0.1 to 10 h, preferably 0.5 to 5 h.

[0028] 8. A method for preparing biochar, comprising the following steps:

[0029] Concentrating the cooking liquid to obtain solids, wherein the solids contain lignin, inorganic salts, hemicellulose and cellulose;

[0030] The solid is carbonized, and optionally washed with a solvent and filtered after carbonization to obtain biochar.

[0031] 9. The method according to item 8, wherein the solvent is selected from any one or more of water, ethanol, methanol, acid solution, and alkaline solution;

[0032] Preferably, the washing temperature is 0 to 100° C., more preferably 60 to 80° C., and the washing time is 0.1 to 120 min, more preferably 30 to 60 min.

[0033] 10. The method according to item 8 or 9, wherein the concentration temperature is 30 to 220°C, preferably 50 to 200°C, and more preferably 70 to 140°C;

[0034] Preferably, the concentration time is 0.1 to 6 hours.

[0035] 11. The method according to any one of items 8 to 10, wherein the solids comprise, based on the total weight of the solids, 5 to 91 wt% of lignin, 1 to 10 wt% of inorganic salts, and 1 to 50 wt% of hemicellulose and cellulose.

[0036] 12. The method according to any one of items 8 to 11, wherein the carbonization temperature is 80 to 800° C., preferably 100 to 500° C.;

[0037] Preferably, the carbonization time is 0.1 to 10 h, preferably 0.5 to 5 h.

[0038] 13. The method according to any one of items 8 to 12, wherein

[0039] Carbonizing the solid to obtain biochar;

[0040] Based on the total weight of the biochar, the biochar comprises: 20 to 89 weight percent of fixed carbon, 10 to 60 weight percent of volatile matter, and 0.5 to 15 weight percent of ash;

[0041] Preferably, the biochar contains 30 to 70 wt % of fixed carbon.

[0042] 14. The method according to claim 13, wherein the ash comprises, based on the total weight of the ash, at least 50 wt% of metal elements, at most 10 wt% of silicon elements, at most 20 wt% of phosphorus elements, and at most 20 wt% of sulfur elements;

[0043] Preferably, the ash contains at least 30 wt% potassium, based on the total weight of the ash.

[0044] 15. The method according to any one of items 8 to 12, wherein

[0045] The solid matter is carbonized, washed with a solvent and filtered to obtain biochar;

[0046] Based on the total weight of the biochar, the biochar comprises: 20 to 89 weight percent of fixed carbon, 10 to 70 weight percent of volatile matter, and 0.1 to 5 weight percent of ash;

[0047] Preferably, the biochar contains 30 to 70 wt % of fixed carbon.

[0048] 16. The method according to claim 15, wherein, based on the total weight of the ash, the ash contains: at least 50 wt% of metal elements, at most 10 wt% of silicon elements, at most 20 wt% of phosphorus elements, and at most 20 wt% of sulfur elements;

[0049] Preferably, the ash contains at least 30 wt% potassium, based on the total weight of the ash.

[0050] 17. A biochar, wherein, based on the total weight of the biochar, the biochar comprises: 20 to 89 weight % of fixed carbon, 10 to 60 weight % of volatile matter, and 0.1 to 15 weight % of ash;

[0051] Preferably, the biochar contains 30 to 70 wt % of fixed carbon.

[0052] 18. The biochar according to claim 17, wherein, based on the total weight of the ash, the ash contains: at least 50 wt% of metal elements, at most 10 wt% of silicon elements, at most 20 wt% of phosphorus elements, and at most 20 wt% of sulfur elements;

[0053] Preferably, the ash contains at least 30 wt% potassium, based on the total weight of the ash.

[0054] 19. A biochar, wherein, based on the total weight of the biochar, the biochar comprises: 20 to 89 weight % of fixed carbon, 10 to 70 weight % of volatile matter, and 0.1 to 5 weight % of ash;

[0055] Preferably, the biochar contains 30 to 70 wt % of fixed carbon.

[0056] 20. The biochar according to claim 19, wherein, based on the total weight of the ash, the ash contains: at least 50 wt% of metal elements, at most 10 wt% of silicon elements, at most 20 wt% of phosphorus elements, and at most 20 wt% of sulfur elements;

[0057] Preferably, the ash contains at least 30 wt% potassium, based on the total weight of the ash.

[0058] 21. The biochar according to any one of items 17 to 20, wherein the calorific value thereof is not less than 4500 kcal / kg.

[0059] 22. Application of biochar in fuel, gasification raw material of gasifier and battery carbon material;

[0060] Preferably, the biomass charcoal is directly used as a fuel or a raw material for gasification of a gasifier; or, the biomass charcoal is crushed and made into a biomass slurry by adding water and a dispersant and then used as a fuel or a raw material for gasification of a gasifier;

[0061] Preferably, the biomass charcoal is used as a battery carbon material after being pre-carbonized, gas-phase deashed, and calcined;

[0062] Preferably, the battery carbon material is a battery hard carbon material;

[0063] Preferably, the battery hard carbon material is a sodium ion battery hard carbon material;

[0064] Preferably, the battery hard carbon material is a battery hard carbon negative electrode material.

[0065] The present application also provides an application of a carbon material in preparing a battery, wherein the carbon material is mainly derived from biomass charcoal.

[0066] Preferably, the biomass charcoal is obtained through calcination, purification, impurity removal and activation treatment;

[0067] Preferably, the carbon material is a battery hard carbon material;

[0068] Preferably, the battery hard carbon material is a sodium ion battery hard carbon material;

[0069] Preferably, the battery hard carbon material is a battery hard carbon negative electrode material.

[0070] Preferably, the biochar is prepared by the following method:

[0071] Concentrating the cooking liquor to obtain solids, wherein the solids contain lignin, salt, hemicellulose and cellulose;

[0072] The solid is dried and carbonized, and optionally washed with a solvent and filtered after the drying and carbonization to obtain biomass charcoal.

[0073] Preferably, the solvent is selected from any one or more of water, ethanol, methanol, acid solution, and alkali solution;

[0074] Preferably, the washing temperature is 0 to 100° C., more preferably 60 to 80° C., and the washing time is 0.1 to 120 min, more preferably 30 to 60 min.

[0075] Preferably, the concentration temperature is 30 to 200°C, preferably 50 to 120°C;

[0076] Preferably, the concentration time is 0.1 to 6 hours.

[0077] Preferably, based on the total weight of the solids, the solids comprise: 5 to 90 wt% of lignin, 1 to 10 wt% of salt, and 1 to 50 wt% of hemicellulose and cellulose.

[0078] Preferably, the drying carbonization temperature is 80 to 500°C, preferably 130 to 300°C.

[0079] The present application also provides a method for preparing biochar, which is characterized by comprising the following steps:

[0080] Concentrating the cooking liquor to obtain solids, wherein the solids contain lignin, salt, hemicellulose and cellulose;

[0081] The solid is dried and carbonized, and optionally washed with a solvent and filtered after the drying and carbonization to obtain biomass charcoal.

[0082] Preferably, the solvent is selected from any one or more of water, ethanol, methanol, acid solution, and alkali solution;

[0083] Preferably, the washing temperature is 0 to 100° C., more preferably 60 to 80° C., and the washing time is 0.1 to 120 min, more preferably 30 to 60 min.

[0084] Preferably, the concentration temperature is 30 to 200°C, preferably 50 to 120°C;

[0085] Preferably, the concentration time is 0.1 to 6 hours.

[0086] Preferably, based on the total weight of the solids, the solids comprise: 5 to 90 wt% of lignin, 1 to 10 wt% of salt, and 1 to 50 wt% of hemicellulose and cellulose.

[0087] Preferably, the drying carbonization temperature is 80 to 500°C, preferably 130 to 300°C.

[0088] Preferably, the solid matter is dried and carbonized to obtain biochar; based on the total weight of the biochar, the biochar comprises: 20 to 90 weight % of fixed carbon, 1 to 60 weight % of volatile matter, and 0 to 15 weight % of ash;

[0089] More preferably, the biochar contains 30 to 70 wt % of fixed carbon.

[0090] Further preferably, the biomass char contains ash, and based on the total weight of the ash, the ash contains: at least 50 weight % of metal elements, at most 10 weight % of silicon elements, at most 20 weight % of phosphorus elements, and at most 20 weight % of sulfur elements;

[0091] More preferably, the biochar contains ash, and the ash contains at least 30 wt% of potassium based on the total weight of the ash.

[0092] Preferably, the solid is dried and carbonized, washed with a solvent and filtered after drying and carbonization to obtain biochar; based on the total weight of the biochar, the biochar contains: 20 to 70 weight % of fixed carbon, 10 to 60 weight % of volatile matter, and 0 to 5 weight % of ash;

[0093] More preferably, the biochar contains 30 to 60 wt % of fixed carbon.

[0094] Further preferably, the biomass char contains ash, and based on the total weight of the ash, the ash contains: at least 50 weight % of metal elements, at most 10 weight % of silicon elements, at most 20 weight % of phosphorus elements, and at most 20 weight % of sulfur elements;

[0095] More preferably, the biochar contains ash, and the ash contains at least 30 wt% of potassium based on the total weight of the ash.

[0096] The present application also provides a biomass charcoal, characterized in that, based on the total weight of the biomass charcoal, the biomass charcoal comprises: 20 to 90 weight % of fixed carbon, 1 to 60 weight % of volatile matter, and 0 to 15 weight % of ash;

[0097] Preferably, the biochar contains 30 to 70 wt % of fixed carbon.

[0098] Preferably, the biomass char contains ash, and based on the total weight of the ash, the ash contains: at least 50 weight % of metal elements, at most 10 weight % of silicon elements, at most 20 weight % of phosphorus elements, and at most 20 weight % of sulfur elements;

[0099] Preferably, the biochar comprises ash, and the ash comprises at least 30 wt% of potassium based on the total weight of the ash.

[0100] The present application also provides a biomass charcoal, characterized in that, based on the total weight of the biomass charcoal, the biomass charcoal comprises: 20 to 70 weight % of fixed carbon, 10 to 60 weight % of volatile matter, and 0 to 5 weight % of ash;

[0101] Preferably, the biochar contains 30-60 wt% of fixed carbon.

[0102] Preferably, the biomass char contains ash, and based on the total weight of the ash, the ash contains: at least 50 weight % of metal elements, at most 10 weight % of silicon elements, at most 20 weight % of phosphorus elements, and at most 20 weight % of sulfur elements;

[0103] Preferably, the biochar comprises ash, and the ash comprises at least 30 wt% of potassium based on the total weight of the ash.

[0104] Preferably, the calorific value of the biochar is not less than 4500 kcal / kg.

[0105] The present application also provides an application of biomass charcoal in fuel, gasification raw material of gasifier, and raw material of battery carbon material;

[0106] Preferably, the biomass char is directly used as fuel or raw material for gasification of a gasifier after simple treatment, or the biomass char is crushed and made into biomass slurry by adding water and a dispersant and then used as fuel or raw material for gasification of a gasifier;

[0107] Preferably, the biomass charcoal is used as a raw material for battery carbon material after calcination, purification, impurity removal and activation treatment;

[0108] Preferably, the battery carbon material is a battery hard carbon material;

[0109] Preferably, the battery hard carbon material is a sodium ion battery hard carbon material;

[0110] Preferably, the battery hard carbon material is a battery hard carbon negative electrode material.

[0111] Effects of the Invention

[0112] (1) The biochar preparation method of the present application is simple to operate, has low carbonization temperature, low energy consumption, low production cost, and significant economic benefits.

[0113] (2) The biochar produced by the method of the present application has a moderate volatile matter content, low sulfur content, uniform particle size, high bulk density, and low ash content. At the same time, it expands the application scope of the biochar and increases the added value of the biochar.

[0114] (3) The biochar prepared by the method of the present application has a high fixed carbon content and a moderate volatile matter content. Therefore, the carbon material for batteries prepared using the biochar has a high yield and good cycle stability. The biochar can also be washed and filtered to obtain biochar with a higher fixed carbon content, thereby preparing a biomass hard carbon material for batteries with high charge and discharge efficiency, large specific capacity, good cycle stability, and excellent sodium insertion and removal capabilities.

[0115] (4) The biochar preparation method of the present application controls the concentration temperature so that the carbonization temperature in the subsequent carbonization process is lower than the conventional carbonization temperature, and the energy consumption is low.

[0116] (5) The ash of the biochar of the present application mainly consists of metal ions, which can effectively improve the stability of the gasification raw materials of the gasifier produced therefrom, and can improve the stability by more than 10%; the sulfur content in the ash is less than 0.3%, which greatly reduces the desulfurization load in the later stage.

[0117] (6) The ash of the biomass charcoal of the present application contains a large amount of metal ions. Using the biomass charcoal of the present application as a precursor of carbon materials for batteries is more conducive to purification, impurity removal, and reduction and adjustment of ash content.

[0118] (7) Biochar contains potassium. After washing and filtering, the liquid portion can be used to prepare high-value-added organic potassium fertilizer to improve economic benefits.

[0119] (8) The biomass charcoal is used as boiler fuel or gasification raw material for gasification furnace, with high calorific value of not less than 4500 kcal / kg, less harmful components, low energy consumption, energy saving and environmental protection, thus realizing the clean and environmentally friendly utilization of biomass energy. BRIEF DESCRIPTION OF THE DRAWINGS

[0120] Figure 1 This is a process flow chart of a specific implementation method of the present application. DETAILED DESCRIPTION

[0121] The specific embodiments of the present application will be described in more detail below with reference to the accompanying drawings. Although the specific embodiments of the present application are shown in the accompanying drawings, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present application and to fully convey the scope of the present application to those skilled in the art.

[0122] It should be noted that the words "including" or "comprising" mentioned throughout the specification and claims are open-ended terms and should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present application, but the description is for the purpose of illustrating the general principles of the present application and is not intended to limit the scope of the present application. The scope of protection of the present application shall be determined by the definition of the attached claims.

[0123] Application related terms

[0124] The "cooking liquid" in this application refers to plant straw (not limited to corn straw, wheat straw, rice straw, reed, rape straw, soybean straw, bagasse, forage grass and other straw), bamboo, wood and other biomass cooked with an organic solvent and then separated into solid and liquid. The liquid part is the cooking liquid, which contains: organic solvent (not limited to formic acid, acetic acid, methanol, ethanol, polyols, etc. or mixtures thereof), lignin, inorganic salts, hemicellulose and cellulose.

[0125] "Gasification in a gasifier" in this application refers to the process in which solid fuels such as biochar, coal, coke or biomass react with a gasifying agent in a gasifier under high temperature, normal pressure or pressurized conditions to convert into gas products and a small amount of residue. The gasifying agent is mainly water vapor, air (or oxygen) or a mixture of them, and the gasification reaction includes a series of homogeneous and heterogeneous chemical reactions. Its main gas product is synthesis gas (with carbon monoxide and hydrogen as the main components).

[0126] The “solid content” in the present application refers to the percentage of solid matter in a liquid to the total weight of the liquid measured at 105° C. using an oven constant weight method.

[0127] The term "carbonization" as used in the present application refers to the high-temperature pyrolysis of biomass raw materials in the absence of oxygen or in the absence of oxygen or in the presence of an inert gas as a protective gas, thereby generating biochar.

[0128] The "pre-carbonization" in this application means that the pyrolysis reaction of biochar at a relatively low temperature is more obvious and the composition of the raw materials changes.

[0129] The "fixed carbon" in this application refers to the residue after removing moisture, ash and volatile matter from biochar, and is measured with reference to the national standard GB / T 212-2008.

[0130] The "biomass carbon powder" in this application refers to biomass carbon with an average particle size D50 less than 200 μm obtained after grinding.

[0131] The "apparent viscosity" in this application refers to the quotient obtained by dividing the corresponding shear stress by the shear rate under a certain velocity gradient, and is measured with reference to the national standard GB / T 18856.4-2002.

[0132] The present application provides a method for preparing biochar, such as Figure 1 As shown, it includes the following steps:

[0133] Concentration: The cooking liquid is concentrated to obtain solids, which contain lignin, inorganic salts, hemicellulose and cellulose;

[0134] Carbonization: The solid matter is carbonized to obtain biochar.

[0135] In the present application, biomass charcoal refers to charcoal derived from biomass, and its source and type are not specifically limited, for example, it can be cooking liquor, papermaking black liquor, etc.

[0136] In a specific embodiment, the method of the present application, based on the total weight of the solids, the solids contain: 5 to 91 weight % of lignin, 1 to 10 weight % of inorganic salts, and 1 to 50 weight % of hemicellulose and cellulose. For example, based on the total weight of the solids, the solids may contain: 5 weight %, 10 weight %, 15 weight %, 20 weight %, 25 weight %, 30 weight %, 35 weight %, 40 weight %, 45 weight %, 50 weight %, 55 weight %, 60 weight %, 65 weight %, 70 weight %, 75 weight %, 80 weight %, 85 weight %, 90 weight %, 91 weight % and the like of lignin; 1 weight %, 2 weight %, 3 weight %, 4 weight %, 5 weight %, 6 weight %, 7 weight %, 8 weight %, 9 weight %, 10 weight %, 15 weight %, 20 weight %, 25 weight %, 30 weight %, 35 weight %, 40 weight %, 45 weight %, 50 weight %, 55 weight %, 60 weight %, 65 weight %, 70 weight %, 75 weight %, 80 weight %, 85 weight %, 90 weight %, 91 weight % and the like of lignin; 0 wt% or more of inorganic salts; 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt%, 18 wt%, 19 wt%, 20 wt%, 21 wt%, 22 wt%, 23 wt%, 24 wt%, 25 wt%, 26 wt%, 27 wt%, 28 wt%, 29 wt%, 30 wt% or more of hemicellulose and cellulose.

[0137] In a specific embodiment, in the method of the present application, the concentration temperature is 30-220°C, preferably 50-200°C, and more preferably 70-140°C, for example, 30, 40, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, etc. Appropriately high concentration temperature makes the obtained biochar have a high fixed carbon content, and the battery electrochemical performance made from the biochar is better; however, for the preparation of water-coal slurry, too high concentration temperature will lead to too low volatile matter of biochar, which is not conducive to subsequent gasification reaction; for battery carbon materials, too high concentration temperature will cause carbon to combine with ash, and it is not easy to wash the ash in the subsequent water washing and acid washing process; in addition, too high concentration temperature will cause the methyl acetic acid in the cooking liquid to decompose and lose solvent.

[0138] In the present application, the concentration is carried out by multi-effect or single-effect falling film evaporation, or by direct or indirect evaporation in an evaporator. The concentration is carried out at different pressures according to different temperatures. When the temperature is below 100°C, the concentration needs to be carried out under vacuum.

[0139] In one embodiment, the concentration temperature is 30 to 200°C; in one embodiment, the concentration temperature is 200 to 220°C. In one embodiment, the concentration temperature is 50 to 120°C. In one embodiment, the concentration temperature is 70 to 120°C. In one embodiment, the concentration temperature is 70 to 200°C. In one embodiment, the concentration temperature is 70 to 110°C. In one embodiment, the concentration temperature is 70 to 100°C. In one embodiment, the concentration temperature is 70 to 90°C. In one embodiment, the concentration temperature is 50 to 110°C. In one embodiment, the concentration temperature is 50 to 100°C. In one embodiment, the concentration temperature is 50 to 90°C.

[0140] In a specific embodiment, the biochar produced by the method of the present application is used as a battery carbon material, and the concentration temperature is 30 to 220°C, preferably 50 to 200°C, more preferably 70 to 140°C, and even more preferably 70 to 110°C.

[0141] In a specific embodiment, the biochar produced by the method of the present application is used as fuel and gasification raw material for a gasifier, and the concentration temperature is 30 to 220°C, preferably 50 to 200°C, more preferably 70 to 130°C, and more preferably 70 to 110°C.

[0142] In a specific embodiment, the concentration temperature is 30-220° C., preferably 50-200° C., more preferably 70-140° C., and the concentration time is 0.1-6 h, for example, 0.1 h, 0.2 h, 0.3 h, 0.4 h, 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, 6 h, etc. In the concentration step, the concentration of the organic acid (formic acid, acetic acid, methanol, ethanol, polyol, etc. or a mixture thereof) in the cooking liquid reaches more than 70%.

[0143] In a specific embodiment, in the method of the present application, the carbonization temperature may be 80 to 800°C, preferably 100 to 500°C, for example, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C. , 270℃, 280℃, 290℃, 300℃, 310℃, 320℃, 330℃, 340℃, 350℃, 360℃, 370℃, 380℃, 390℃, 400℃, 410℃, 420℃, 430℃, 440℃, 450℃, 460℃, 470℃, 480℃, 490℃, 500℃, 600℃, 700℃, 800℃, etc. The carbonization temperature of the present application is lower than the conventional carbonization temperature. The carbonization temperature within this range makes the volatile matter content in the carbonization stage moderate, which is beneficial as a raw material for gasification in a gasifier and a battery carbon material, while reducing energy consumption and saving energy. For the raw materials of gasification in gasifiers, too high carbonization temperature will lead to low volatile matter of the biochar produced, which is not conducive to being used as raw materials for gasification in gasifiers, and the gasification yield is low; too low carbonization temperature will lead to too high volatile matter and low fixed carbon content of the biochar produced, which will reduce the yield and production efficiency of the raw materials gasification in gasifiers. For battery materials, high carbonization temperature will reduce the percentage of volatile matter (mainly carbohydrates), thereby increasing the percentage of fixed carbon, but the temperature should not be too high. Too high temperature will cause the carbon to combine with the ash for battery carbon materials, and it will be difficult to wash off the ash in the subsequent water washing and acid washing process.

[0144] The carbonization of the present application is carried out under the protection of an inert gas, and any existing dry carbonization equipment can be applied.

[0145] In one embodiment, the carbonization temperature is 130-300°C; in one embodiment, the carbonization temperature is 130-200°C; in one embodiment, the carbonization temperature is 130-500°C; in one embodiment, the carbonization temperature is 300-500°C; in one embodiment, the carbonization temperature is 200-300°C; in one embodiment, the carbonization temperature is 80-130°C; in one embodiment, the carbonization temperature is 80-300°C; in one embodiment, the carbonization temperature is 100-130°C; in one embodiment, the carbonization temperature is 130-500°C;.

[0146] In a specific embodiment, the biochar produced by the method of the present application is used as a battery carbon material, and the carbonization temperature is 80 to 800°C, preferably 100 to 500°C, and more preferably 130 to 500°C.

[0147] In a specific embodiment, the biochar produced by the method of the present application is used as fuel and gasification raw material for a gasifier, and the carbonization temperature is 80-800°C, preferably 100-500°C, preferably 130-500°C, and more preferably 130-180°C.

[0148] In a specific embodiment, the carbonization temperature can be 80-800°C, preferably 100-500°C, and the carbonization time is 0.1-10h, for example, 0.1h, 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, etc., preferably 0.5-5h. The carbonization time of the present application is short, which reduces energy consumption and saves energy.

[0149] In a specific embodiment, the method of the present application directly obtains biochar after carbonizing the solid. Based on the total weight of the biochar, the biochar contains: 20-89 weight% of fixed carbon, for example, 20 weight%, 30 weight%, 40 weight%, 50 weight%, 60 weight%, 70 weight%, 80 weight%, 89 weight%, etc.; 10-60 weight% of volatile matter, for example, 10 weight%, 15 weight%, 20 weight%, 25 weight%, 30 weight%, 35 weight%, 40 weight%, 45 weight%, 50 weight%, 55 weight%, 60 weight%, etc.; and 0.5-15 weight% of ash, for example, 0.5 weight%, 1 weight%, 2 weight%, 4 weight%, 6 weight%, 8 weight%, 10 weight%, 12 weight%, 14 weight%, 15 weight%, etc. In one embodiment, the biochar contains 1 to 60% by weight of volatile matter; in one embodiment, the biochar contains 1 to 10% by weight of volatile matter. In one embodiment, the biochar contains 20 to 30% by weight of volatile matter. In one embodiment, the biochar contains 30 to 40% by weight of volatile matter. In one embodiment, the biochar contains 40 to 50% by weight of volatile matter. In one embodiment, the biochar contains 50 to 60% by weight of volatile matter. In one embodiment, the biochar contains 30 to 40% by weight of volatile matter. In one embodiment, the biochar contains 20 to 60% by weight of volatile matter. In one embodiment, the biochar contains 20 to 50% by weight of volatile matter. In one embodiment, the biochar contains 30 to 60% by weight of volatile matter. In one embodiment, the biochar contains 30 to 50% by weight of volatile matter.

[0150] In a specific embodiment, the method of the present application carbonizes the solid to obtain biochar, based on the total weight of the biochar, the biochar contains: 20-89 weight % of fixed carbon, 10-60 weight % of volatile matter, 0.5-15 weight % of ash, based on the total weight of the ash, the ash contains: at least 50 weight % of metal elements, for example, 50 weight %, 60 weight %, 70 weight %, 80 weight %, 83 weight %, 86 weight %, 89 weight %, 92 weight %, 95 weight %, 98 weight %, 99 weight %, etc., and up to 10 weight % of silicon, for example, 0.5 weight %, 1 weight %, 1.5 weight %, 2 weight %, 3 weight %, 4 weight %, 5 weight %, 6 weight %, %, 7% by weight, 8% by weight, 9% by weight, 10% by weight, etc., and up to 20% by weight of phosphorus, for example, 1% by weight, 3% by weight, 5% by weight, 7% by weight, 9% by weight, 11% by weight, 13% by weight, 15% by weight, 17% by weight, 19% by weight, 20% by weight, etc., and up to 20% by weight of sulfur, for example, 1% by weight, 3% by weight, 5% by weight, 7% by weight, 9% by weight, 11% by weight, 13% by weight, 15% by weight, 17% by weight, 19% by weight, 20% by weight, etc.; wherein at least 30% of the mass of the ash is potassium, for example, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 94%, 96%, 98%, etc., and the potassium contained can be used to produce potash fertilizer later. Ash contains a large amount of metal ions, which is beneficial to the stability of biomass slurry, can improve the stability by more than 10%, and is beneficial to the purification and removal of impurities of carbon materials for batteries.

[0151] In a specific embodiment, Figure 1 As shown, the method for preparing biochar provided in the present application comprises the following steps:

[0152] Concentration: The cooking liquid is concentrated to obtain solids, which contain lignin, inorganic salts, hemicellulose and cellulose;

[0153] Carbonization: carbonizing the solid matter;

[0154] Washing: After carbonization, the solid part is washed with a solvent and filtered to obtain biochar.

[0155] In the above specific embodiment, the solvent is selected from any one or more of water, ethanol, methanol, acid solution, and alkaline solution, preferably water or acid solution.

[0156] In a specific embodiment, when the biochar produced by the method of the present application is used as a battery carbon material, the solvent used for washing in the method of the present application is an acid solution, preferably an acetic acid solution.

[0157] The present application does not specifically limit the washing time and washing temperature, as long as the soluble inorganic salts in the biochar can be fully dissolved in the washing liquid. In a specific embodiment, the washing temperature is 0 to 100°C, preferably 60 to 80°C, for example, 0°C, 5°C, 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, etc.; the washing time is 0.1 to 120 minutes, preferably 30 to 60 minutes, for example, 0.1 minutes, 1 minutes, 3 minutes, 6 minutes, 9 minutes, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, 60 minutes, 70 minutes, 80 minutes, 90 minutes, 100 minutes, 110 minutes, 120 minutes, etc.

[0158] In a specific embodiment, the washing can be single-stage washing or multi-stage washing (for example, it can be two-stage washing, three-stage washing, four-stage washing, etc.), preferably multi-stage washing; the washing temperature is 0-100°C, preferably 60-80°C, for example, it can be 0°C, 5°C, 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, etc.; the washing time is 0.1-120min, preferably 30-60min, for example, it can be 0.1min, 1min, 3min, 6min, 9min, 10min, 20min, 30min, 40min, 50min, 60min, 70min, 80min, 90min, 100min, 110min, 120min, etc. In a preferred embodiment, the washing time is 30-60min and the washing temperature is 60-80°C. The ash content percentage of the washed biomass charcoal obtained after washing and filtration in the present application is reduced, and the fixed carbon content percentage is correspondingly increased, which is conducive to obtaining gasification furnace gasification raw materials with high calorific value, low ash content and high slurry concentration, as well as battery carbon materials with higher charge and discharge efficiency and better cycle stability, especially hard carbon negative electrode materials for sodium ion batteries.

[0159] In a specific embodiment, the method of the present application, after carbonizing the solid, washing and filtering with a solvent to obtain biochar, based on the total weight of the biochar, the biochar comprises: 20 to 89 weight% of fixed carbon, for example, 20 weight%, 30 weight%, 35 weight%, 40 weight%, 45 weight%, 50 weight%, 55 weight%, 60 weight%, 65 weight%, 70 weight%, 75 weight%, 80 weight%, 85 weight%, 89 weight%, etc.; 10 to 70 weight% of volatile matter, for example, 10 weight%, 15 weight%, 20 weight%, 25 weight%, 30 weight%, 45 weight%, 50 weight%, 55 weight%, 60 weight%, 65 weight%, 70 weight%, 75 weight%, 80 weight%, 85 weight%, 89 weight%, etc. %, 35% by weight, 40% by weight, 45% by weight, 50% by weight, 55% by weight, 60% by weight, 65% by weight, 70% by weight, etc.; and 0.1-5% by weight of ash, for example, 0.1% by weight, 0.4% by weight, 0.8% by weight, 1.2% by weight, 1.6% by weight, 0.8% by weight, 1% by weight, 1.2% by weight, 1.4% by weight, 1.6% by weight, 1.8% by weight, 2% by weight, 2.0% by weight, 2.4% by weight, 2.8% by weight, 3.2% by weight, 3.6% by weight, 4.0% by weight, 4.4% by weight, 4.8% by weight, 5.0% by weight, etc. In one embodiment, the biochar contains 20-70% by weight of fixed carbon; in one embodiment, the biochar contains 70-89% by weight of fixed carbon. In one embodiment, the biochar contains 10-20% by weight of volatile matter. In a specific embodiment, the biochar contains 20 to 30% by weight of volatile matter. In a specific embodiment, the biochar contains 30 to 40% by weight of volatile matter. In a specific embodiment, the biochar contains 40 to 50% by weight of volatile matter. In a specific embodiment, the biochar contains 50 to 60% by weight of volatile matter. In a specific embodiment, the biochar contains 30 to 40% by weight of volatile matter. In a specific embodiment, the biochar contains 20 to 60% by weight of volatile matter. In a specific embodiment, the biochar contains 20 to 50% by weight of volatile matter. In a specific embodiment, the biochar contains 30 to 60% by weight of volatile matter. In a specific embodiment, the biochar contains 30 to 50% by weight of volatile matter.

[0160] In the above specific embodiment, based on the total weight of the ash, the ash contains: at least 50 weight % of metal elements, such as 50 weight %, 60 weight %, 70 weight %, 80 weight %, 83 weight %, 86 weight %, 89 weight %, 92 weight %, 95 weight %, 98 weight %, 99 weight %, etc., and at most 10 weight % of silicon element, such as 0.5 weight %, 1 weight %, 1.5 weight %, 2 weight %, 3 weight %, 4 weight %, 5 weight %, 6 weight %, 7 weight %, 8 weight %, 9 weight %, 10 weight %, etc., and at most 20 weight % of phosphorus element %, for example, 1 wt. %, 3 wt. %, 5 wt. %, 7 wt. %, 9 wt. %, 11 wt. %, 13 wt. %, 15 wt. %, 17 wt. %, 19 wt. %, 20 wt. %, etc., and up to 20 wt. % of elemental sulfur, for example, 1 wt. %, 3 wt. %, 5 wt. %, 7 wt. %, 9 wt. %, 11 wt. %, 13 wt. %, 15 wt. %, 17 wt. %, 19 wt. %, 20 wt. %, etc.; wherein at least 30 % by mass of the ash is elemental potassium, for example, 30 wt. %, 40 wt. %, 50 wt. %, 60 wt. %, 70 wt. %, 80 wt. %, 90 wt. %, 94 wt. %, 96 wt. %, 98 wt. %, etc.

[0161] On the other hand, the present application also provides an application of biochar in fuel, gasification raw material for gasifiers, and battery carbon materials.

[0162] In a specific embodiment, the gasification raw material of the gasifier may be water-coal slurry.

[0163] In a specific embodiment, the biomass charcoal of the present application can be used directly as fuel or gasification raw material for a gasifier, or used as fuel or gasification raw material for a gasifier after simple treatment, or used as fuel or gasification raw material for a gasifier after being crushed and made into biomass slurry by adding water and a dispersant.

[0164] In a specific embodiment, the biomass char obtained after the aforementioned concentration and carbonization steps of the present application can be crushed and pulped with water and a dispersant to make a biomass slurry for use as fuel or a gasification raw material for a gasifier. For example, the pulping step is: grinding the biomass char to obtain a biomass char powder 1, adding water and a dispersant to prepare a biomass slurry 1, which is used as a fuel or a gasification raw material for a gasifier, wherein the mass of the added dispersant is 0.1% to 0.5% of the mass of the biomass slurry 1.

[0165] In a specific embodiment, the biomass char obtained after the aforementioned concentration, carbonization, and washing steps of the present application can be crushed and pulped with water and a dispersant to make a biomass slurry for use as fuel or a gasification raw material for a gasifier. For example, the pulping step is: after grinding the biomass char to obtain biomass char powder II, water and a dispersant are added to prepare a biomass slurry II for use as a fuel or a gasification raw material for a gasifier, wherein the mass of the added dispersant is 0.1% to 0.5% of the mass of the biomass slurry II.

[0166] The present application also provides a biomass slurry prepared by any of the aforementioned methods.

[0167] Compared with the biomass slurry made from the biomass charcoal obtained after carbonization but not washed with a solvent and filtered, the slurry concentration of the biomass slurry made from the biomass charcoal obtained after carbonization and washed with a solvent and filtered is 2% to 5% higher.

[0168] The dispersant of the present application refers to a surfactant that can stably disperse biomass carbon powder in water without stratification and precipitation within a certain period of time. It can also reduce the apparent viscosity of the biomass slurry. In a specific embodiment, the dispersant can be selected from: naphthalenesulfonate dispersant, lignin sulfonate dispersant, etc.

[0169] Compared with the biomass charcoal obtained after the aforementioned concentration and carbonization steps of the present application, the biomass charcoal obtained after the aforementioned concentration, carbonization and washing steps of the present application has a higher fixed carbon content and a lower ash content, and can be used to prepare fuels with higher calorific value and lower ash content and gasification raw materials for gasification furnaces, as well as biomass slurry with higher slurry concentration, and biomass hard carbon negative electrode materials for sodium ion batteries with higher charge and discharge efficiency and better cycle stability.

[0170] In a specific embodiment, the biomass charcoal of the present application is used as a biomass hard carbon negative electrode material for sodium ion batteries after pre-carbonization, gas phase deashing, calcination and other steps. Specifically, the following steps may be included:

[0171] (1) crushing the biochar into biochar particles; in an inert gas atmosphere, heating the biochar particles to 300-800° C. for pre-carbonization for 1-3 hours, then cooling to room temperature, and then crushing the pre-carbonized carbon material to obtain an intermediate product;

[0172] (2) the intermediate product obtained in step (1) is subjected to gas phase deashing in an inert gas atmosphere and in an atmosphere of halogen elements and / or halogen compounds such as chlorine and / or hydrogen chloride, wherein the gas phase deashing temperature is 600 to 1200° C., the gas phase deashing time is 20 to 200 min, and the volume ratio of the inert gas to the halogen elements and / or halogen compounds is 0.1 to 6:100, and a purified semi-finished product is obtained after gas phase deashing;

[0173] (3) The purified semi-finished product obtained in step (2) is crushed into particles with an average particle size of 1 to 20 μm, and calcined at 1000 to 1500° C. for 0.5 to 5 hours under an inert gas protective atmosphere to obtain a hard carbon negative electrode material for a sodium ion battery.

[0174] The biomass hard carbon negative electrode material for sodium ion batteries prepared using the biomass carbon of the present application has high charge and discharge efficiency, large specific capacity, good cycle stability, and excellent sodium insertion and removal capabilities.

[0175] Compared with the hard carbon negative electrode material for sodium ion batteries made from biomass charcoal obtained after carbonization but not washed with solvent and filtered, the hard carbon negative electrode material for sodium ion batteries made from biomass charcoal obtained after carbonization but washed with solvent and filtered has a first charge and discharge efficiency 2% to 4% higher, a first discharge specific capacity 10 to 25 mAh / g higher, and better cycle stability.

[0176] The present application also provides an application of a carbon material in preparing a battery, wherein the carbon material is prepared from biomass charcoal.

[0177] In a specific embodiment, the biomass charcoal is subjected to pre-carbonization, gas phase deashing and calcination to obtain the carbon material; the carbon material may be a battery hard carbon material; the battery hard carbon material may be a sodium ion battery hard carbon material; the sodium ion battery hard carbon material may be a sodium ion battery hard carbon negative electrode material.

[0178] In a specific embodiment, the biochar is prepared by any of the aforementioned methods for preparing biochar.

[0179] In addition, the present application also provides biochar prepared by any of the above methods for preparing biochar. In a specific embodiment, the calorific value of the biochar of the present application is not less than 4500 kcal / kg.

[0180] In order to make the purpose, technical solutions and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with specific embodiments.

[0181] Example

[0182] In the following specific implementation manner, the sources of some materials and reagents are shown in Table 1 below.

[0183] Table 1

[0184]

[0185] The method for determining the content of lignin in the solid matter of the present application is: infrared spectroscopy, specifically referring to the third part of "Lignin" edited by Jiang Tingda and published by Chemical Industry Press.

[0186] The method for determining the content of inorganic salt in the solid matter of the present application is: Inductively Coupled Plasma Atomic Emission Spectrometry (ICP-AES).

[0187] The determination method of hemicellulose and cellulose in the solids of the present application is: distillation aldehyde test, specifically referring to the determination method of pentosan for papermaking raw materials GB / T2677.9-1994.

[0188] The method for determining the fixed carbon, volatile matter and ash in the biochar, water-washed biochar and acid-washed biochar of the present application is as follows: determination is carried out with reference to the national standard GB / T 212-2008.

[0189] The apparent viscosity of the biomass slurry prepared from the biomass charcoal of the present application is measured with reference to the national standard GB / T18856.4-2002.

[0190] The concentration of the biomass slurry prepared from the biochar of the present application is measured with reference to the national standard GB / T18856.2-2002.

[0191] The calorific value of the biochar in the present application is determined in accordance with the national standard GB / T 213-2008.

[0192] The contents described in the examples of this application are all weight percentages.

[0193] The specific surface area of ​​the battery hard carbon material of the present application is determined with reference to the national standard GB / T 19587-2017.

[0194] Calculation method for the yield of battery hard carbon negative electrode material: dry mass of battery hard carbon negative electrode material ÷ mass of hard carbon precursor (mass of dry biochar after drying or washing with dry solvent) × 100%

[0195] Example 1

[0196] Weigh 10kg of cooking liquid with a solid content of 10.15%, and concentrate it with a single-effect falling film evaporator at 70°C and its saturation pressure for 5 hours to obtain 954g of solids, which contain: 83% lignin, 2% inorganic salts, 15% hemicellulose and cellulose. The solids are carbonized at 130°C for 2 hours to obtain 868g of biochar. The biochar contains 45% fixed carbon, 47% volatile matter, 8% ash, and a calorific value of 4980kcal / kg.

[0197] 400 g of biochar was weighed and ground, and water and 0.1% of the mass of the final biomass slurry naphthalenesulfonate dispersant were added. The prepared biomass slurry had a slurry concentration of 61% and an apparent viscosity of 460 cp.

[0198] 400 g of biochar was weighed and ground, and the biochar was pre-carbonized at 450 ° C for 2 hours under a nitrogen atmosphere, and then the pre-carbonized carbon material was crushed to obtain an intermediate product; the intermediate product was gas-phase deashed at 900 ° C for 1.5 hours, during which a mixed gas of chlorine and nitrogen with a volume ratio of 1:100 was introduced to obtain a purified semi-finished product; the purified semi-finished product was crushed into particles with a D50 of 8 μm by a gas flow mill, and then high-temperature calcined at 1200 ° C for 2 hours under a nitrogen atmosphere to obtain a battery hard carbon material with a total yield of 41% and a specific surface area of ​​4.2 m 2 / g. The battery's gram capacity is 308mAh / g, and the battery's first coulombic efficiency is 89%.

[0199] Example 2

[0200] Weigh 10kg of cooking liquid with a solid content of 10.15%, and concentrate it with a single-effect falling film evaporator at 110℃ and its saturated pressure for 5h to obtain 945g of solids, which contain: 86% lignin, 2% inorganic salts, 12% hemicellulose and cellulose. The solids are carbonized at 130℃ for 2h to obtain 858g of biochar. The biochar contains 50% fixed carbon, 44% volatile matter, 6% ash, and a calorific value of 5090kcal / kg.

[0201] 400 g of biochar was weighed and ground, and water and 0.1% of the mass of the final biomass slurry naphthalenesulfonate dispersant were added. The prepared biomass slurry had a slurry concentration of 62% and an apparent viscosity of 480 cp.

[0202] 400 g of biochar was weighed and ground, and the biochar was pre-carbonized at 450 ° C for 2 hours under a nitrogen atmosphere, and then the pre-carbonized carbon material was crushed to obtain an intermediate product; the intermediate product was gas-phase deashed at 900 ° C for 1.5 hours, during which a mixed gas of chlorine and nitrogen with a volume ratio of 1:100 was introduced to obtain a purified semi-finished product; the purified semi-finished product was crushed into particles with a D50 of 8 μm by a gas flow mill, and then high-temperature calcined at 1200 ° C for 2 hours under a nitrogen atmosphere to obtain a battery hard carbon material with a total yield of 44% and a specific surface area of ​​3.9 m 2 / g. The battery capacity is 309mAh / g, and the first coulombic efficiency is 90%.

[0203] Example 3

[0204] Weigh 10kg of cooking liquid with a solid content of 10.15%, and concentrate it for 3 hours at 70℃ and its saturated pressure using a single-effect falling film evaporator to obtain 965g of solids, which contain: 79% lignin, 3% inorganic salts, 18% hemicellulose and cellulose. The solids are carbonized at 180℃ for 2 hours to obtain 886g of biochar. The biochar is washed with water at three levels, with a washing temperature of 60℃ and a washing time of 30min, to obtain 805g of washed biochar. The washed biochar contains 46% fixed carbon, 51% volatile matter, 3% ash, and a calorific value of 4980kcal / kg.

[0205] 400 g of washed biochar was weighed and ground, and water and 0.1% of the mass of the final biomass slurry naphthalenesulfonate dispersant were added to prepare the biomass slurry with a slurry concentration of 63% and an apparent viscosity of 520 cp.

[0206] 400 g of washed biochar was weighed and ground, and the biochar was pre-carbonized at 450 ° C for 2 hours under a nitrogen atmosphere, and then the pre-carbonized carbon material was crushed to obtain an intermediate product; the intermediate product was gas-phase deashed at 900 ° C for 1.5 hours, during which a mixed gas of chlorine and nitrogen with a volume ratio of 1:100 was introduced to obtain a purified semi-finished product; the purified semi-finished product was crushed into particles with a D50 of 8 μm by a gas flow mill, and then high-temperature calcined at 1200 ° C for 2 hours under a nitrogen atmosphere to obtain a battery hard carbon material with a total yield of 42% and a specific surface area of ​​3.8 m 2 / g. The battery's gram capacity is 314mAh / g, and the battery's first coulombic efficiency is 91%.

[0207] Example 4

[0208] Weigh 10kg of cooking liquid with a solid content of 10.15%, and concentrate it for 3 hours at 90℃ and its saturated pressure using a single-effect falling film evaporator to obtain 948g of solids, which contain: 82% lignin, 3% inorganic salts, 15% hemicellulose and cellulose. The solids are carbonized at 180℃ for 2 hours to obtain 873g of biochar. The biochar is washed with water at three levels, with a washing temperature of 60℃ and a washing time of 30min, to obtain 790g of washed biochar. The washed biochar contains 48% fixed carbon, 49.4% volatile matter, 2.6% ash, and a calorific value of 5000kcal / kg.

[0209] 350 g of washed biochar was weighed and ground, and water and 0.1% of the mass of the final biomass slurry naphthalenesulfonate dispersant were added to prepare the biomass slurry with a slurry concentration of 63.5% and an apparent viscosity of 530 cp.

[0210] 350 g of washed biochar was weighed and ground, and the biochar was pre-carbonized at 450 ° C for 2 hours under a nitrogen atmosphere, and then the pre-carbonized carbon material was crushed to obtain an intermediate product; the intermediate product was gas-phase deashed at 900 ° C for 1.5 hours, during which a mixed gas of chlorine and nitrogen with a volume ratio of 1:100 was introduced to obtain a purified semi-finished product; the purified semi-finished product was crushed into particles with a D50 of 8 μm by a gas flow mill, and then high-temperature calcined at 1200 ° C for 2 hours under a nitrogen atmosphere to obtain a battery hard carbon material with a total yield of 43% and a specific surface area of ​​3.6 m 2 / g. The battery's gram capacity is 318mAh / g, and the battery's first coulombic efficiency is 94%.

[0211] Example 5

[0212] Weigh 10kg of cooking liquid with a solid content of 10.15%, and concentrate it for 3 hours at 130℃ and its saturated pressure using a single-effect falling film evaporator to obtain 930g of solids, which contain: 88% lignin, 4% inorganic salts, 8% hemicellulose and cellulose. The solids are carbonized at 180℃ for 2 hours to obtain 853g of biochar. The biochar is washed with water at three levels, with a washing temperature of 60℃ and a washing time of 30min, to obtain 782g of washed biochar. The washed biochar contains 50% fixed carbon, 47.6% volatile matter, 2.4% ash, and a calorific value of 5120kcal / kg.

[0213] 350 g of washed biochar was weighed and ground, and water and 0.1% of the mass of the final biomass slurry naphthalenesulfonate dispersant were added to prepare the biomass slurry with a slurry concentration of 60.3% and an apparent viscosity of 535 cp.

[0214] 350 g of washed biochar was weighed and ground, and the biochar was pre-carbonized at 450 ° C for 2 hours under a nitrogen atmosphere, and then the pre-carbonized carbon material was crushed to obtain an intermediate product; the intermediate product was gas-phase deashed at 900 ° C for 1.5 hours, during which a mixed gas of chlorine and nitrogen with a volume ratio of 1:100 was introduced to obtain a purified semi-finished product; the purified semi-finished product was crushed into particles with a D50 of 8 μm by a gas flow mill, and then high-temperature calcined at 1200 ° C for 2 hours under a nitrogen atmosphere to obtain a battery hard carbon material with a total yield of 43% and a specific surface area of ​​3.7 m 2 / g. The battery's gram capacity is 301mAh / g, and the battery's first coulombic efficiency is 89%.

[0215] Example 6

[0216] Weigh 10kg of cooking liquid with a solid content of 10.15%, and concentrate it for 3 hours at 60℃ and its saturated pressure using a single-effect falling film evaporator to obtain 1042g of solids, which contain: 73% lignin, 2% inorganic salts, 21% hemicellulose and cellulose. The solids are carbonized at 180℃ for 2 hours to obtain 593g of biochar. The biochar is washed with three levels of water at a washing temperature of 60℃ and a washing time of 30min to obtain 533g of washed biochar. The washed biochar contains 40% fixed carbon, 56.3% volatile matter, 3.7% ash, and a calorific value of 4880kcal / kg.

[0217] 250 g of washed biochar was weighed and ground, and water and 0.1% of the mass of the final biomass slurry naphthalenesulfonate dispersant were added to prepare the biomass slurry with a slurry concentration of 55% and an apparent viscosity of 360 cp.

[0218] Weigh 250g of washed biochar and grind it, pre-carbonize the biochar at 450℃ for 2 hours under a nitrogen atmosphere, and then crush the pre-carbonized carbon material to obtain an intermediate product 1; gas phase deash the intermediate product 1 at 900℃ for 1.5 hours, during which a mixed gas of chlorine and nitrogen with a volume ratio of 1:100 is introduced to obtain a purified semi-finished product 2; the purified semi-finished product 2 is crushed into particles with a D50 of 8μm by a gas flow mill, and then high-temperature calcined at 1200℃ for 2h under a nitrogen atmosphere to obtain a battery hard carbon material with a total yield of 38% and a specific surface area of ​​4.4m 2 / g. The battery's gram capacity is 297mAh / g, and the battery's first coulombic efficiency is 87%.

[0219] Example 7

[0220] Weigh 10kg of cooking liquid with a solid content of 10.15%, and concentrate it for 3 hours at 140℃ and its saturated pressure using a single-effect falling film evaporator to obtain 910g of solids, which contain: 90% lignin, 5% inorganic salts, 5% hemicellulose and cellulose. The solids are carbonized at 180℃ for 2 hours to obtain 579g of biochar. The biochar is washed with three levels of water at a washing temperature of 60℃ and a washing time of 30min to obtain 520g of washed biochar. The washed biochar contains 54% fixed carbon, 43.5% volatile matter, 2.5% ash, and a calorific value of 5110kcal / kg.

[0221] 260 g of washed biochar was weighed and ground, and water and 0.1% of the mass of the final biomass slurry naphthalenesulfonate dispersant were added to prepare the biomass slurry with a slurry concentration of 60.4% and an apparent viscosity of 680 cp.

[0222] 260 g of washed biochar was weighed and ground, and the biochar was pre-carbonized at 450 ° C for 2 hours under a nitrogen atmosphere, and then the pre-carbonized carbon material was crushed to obtain an intermediate product 1; the intermediate product 1 was gas-phase deashed at 900 ° C for 1.5 hours, during which a mixed gas of chlorine and nitrogen with a volume ratio of 1:100 was introduced to obtain a purified semi-finished product 2; the purified semi-finished product 2 was crushed into particles with a D50 of 8 μm by a gas flow mill, and then high-temperature calcined at 1200 ° C for 2 hours under a nitrogen atmosphere to obtain a battery hard carbon material with a total yield of 48% and a specific surface area of ​​3.9 m 2 / g. The battery's gram capacity is 305mAh / g, and the battery's first coulombic efficiency is 90%.

[0223] Example 8

[0224] The difference between this embodiment and embodiment 1 is that after obtaining the biochar, the biochar is subjected to three-stage water washing at a washing temperature of 60° C. and a washing time of 30 min to obtain the washed biochar.

[0225] Example 9

[0226] The difference between this embodiment and embodiment 1 is that after obtaining the biochar, the biochar is washed with a three-stage 10% acetic acid solution at a washing temperature of 60° C. for 30 minutes to obtain the acid-washed biochar.

[0227] Example 10

[0228] The difference between this embodiment and embodiment 9 is that the concentration temperature is 110°C.

[0229] Embodiment 11

[0230] The difference between this embodiment and embodiment 9 is that the concentration temperature is 50°C.

[0231] Example 12

[0232] The difference between this embodiment and embodiment 9 is that the concentration temperature is 30°C.

[0233] Example 13

[0234] The difference between this embodiment and embodiment 9 is that the concentration temperature is 140°C.

[0235] Embodiment 14

[0236] Weigh 10kg of cooking liquor with a solid content of 10.15%, and concentrate it with a single-effect falling film evaporator at 70°C and its saturated pressure for 5h to obtain 954g of solids, which contain: 83% lignin, 2% inorganic salts, 15% hemicellulose and cellulose. The solids are carbonized at 80°C for 2h to obtain 698g of biochar. The biochar is washed with a three-stage 10% acetic acid solution at a washing temperature of 60°C and a washing time of 30min to obtain 692g of acid-washed biochar. The acid-washed biochar contains 36% fixed carbon, 63.6% volatile matter, 0.4% ash, and a calorific value of 4780kcal / kg.

[0237] 340 g of washed biochar was weighed and ground, and water and 0.1% of the mass of the final biomass slurry naphthalenesulfonate dispersant were added to prepare the biomass slurry with a slurry concentration of 58% and an apparent viscosity of 465 cp.

[0238] 340 g of washed biochar was weighed and ground, and the ground biochar was pre-carbonized at 450 ° C for 2 hours under a nitrogen atmosphere, and the pre-carbonized carbon material was crushed to obtain an intermediate product; the intermediate product was gas-phase deashed at 900 ° C for 1.5 hours, during which a mixed gas of chlorine and nitrogen with a volume ratio of 1:100 was introduced to obtain a purified semi-finished product; the purified semi-finished product was crushed into particles with a D50 of 8 μm by a gas flow mill, and then high-temperature calcined at 1200 ° C for 2 hours under a nitrogen atmosphere to obtain a battery hard carbon material with a total yield of 30% and a specific surface area of ​​4.3 m 2 / g. The battery's gram capacity is 289mAh / g, and the battery's first coulombic efficiency is 87%.

[0239] Embodiment 15

[0240] The difference between this embodiment and embodiment 14 is that the carbonization temperature is 500°C.

[0241] Example 16

[0242] The difference between this embodiment and embodiment 14 is that the carbonization temperature is 110°C.

[0243] Embodiment 17

[0244] The difference between this embodiment and embodiment 14 is that the carbonization temperature is 160°C.

[0245] Embodiment 18

[0246] The difference between this embodiment and embodiment 9 is that the cooking liquor is replaced by papermaking black liquor.

[0247] Embodiment 19

[0248] The difference between this embodiment and embodiment 14 is that the carbonization temperature is 800° C. The performance of the water-coal slurry prepared from the biochar in this embodiment and the electrochemical performance of the prepared battery are both excellent, but due to the low volatile content of the biochar, the gasification rate is relatively low.

[0249] Comparative Example 1

[0250] Weigh 10kg of cooking liquid with a solid content of 10.15%, and obtain 867g of biochar after low-temperature carbonization at 130℃ for 2h. The biochar is washed with water at 60℃ for 30min to obtain 860g of washed biochar. The washed biochar contains 28% fixed carbon, 67.3% volatile matter, 4.7% ash, and a calorific value of 4860kcal / kg.

[0251] 400 g of washed biochar was weighed and ground, and water and 0.1% of the mass of the final biomass slurry naphthalenesulfonate dispersant were added to prepare the biomass slurry with a slurry concentration of 54% and an apparent viscosity of 456 cp.

[0252] 400 g of washed biochar was weighed and ground, and the biochar was pre-carbonized at 450 ° C for 2 hours under a nitrogen atmosphere, and then the pre-carbonized carbon material was crushed to obtain an intermediate product; the intermediate product was gas-phase deashed at 900 ° C for 1.5 hours, during which a mixed gas of chlorine and nitrogen with a volume ratio of 1:100 was introduced to obtain a purified semi-finished product; the purified semi-finished product was crushed into particles with a D50 of 8 μm by a gas flow mill, and then high-temperature calcined at 1200 ° C for 2 hours under a nitrogen atmosphere to obtain a battery hard carbon material with a total yield of 35% and a specific surface area of ​​4.5 m 2 / g. The battery's gram capacity is 279mAh / g, and the battery's first coulombic efficiency is 82%.

[0253] The battery hard carbon materials of each embodiment and comparative example are used to prepare batteries. The specific preparation method and the determination method of the battery gram capacity and the first coulomb efficiency are as follows:

[0254] A slurry of 96 parts of hard carbon material, 1.5 parts of CMC, 1.5 parts of SBR and 1 part of SP mixed with water was evenly coated on the copper foil, baked in an oven at 90°C for 30-40 minutes, and cut into 12mm diameter discs to obtain an active material loading of 3-3.5mg / cm 2 The electrode pole piece was then prepared in a glove box with a protective gas atmosphere. The electrolyte was 1.5MNaPF6 (the volume ratio of EC:DEC:EMC was 1:2:2), the separator was glass fiber (GF / A), and the positive electrode was a sodium sheet.

[0255] For the half-cell prepared as above, the charge and discharge of the half-cell was tested using a battery testing device (manufactured by Wuhan Blue Electric). The process of embedding sodium ions into the hard carbon negative electrode is called "discharge", and the process of de-embedding sodium ions from the hard carbon negative electrode is called "charge". During the test, the half-cell was first allowed to stand for 8 hours, and then discharged to 0V using a constant current of 0.1C (about 30mA / g). When the voltage reached 0V, constant voltage discharge was performed at 0V until the current value reached 0.01mA. The value obtained by dividing the amount of electricity supplied by the load of the hard carbon material on the electrode was the discharge capacity of the hard carbon (mAh / g). After the discharge was completed, the battery was allowed to stand for 10 minutes, and then sodium ions were de-embedded from the negative electrode. The battery was charged to 2V at a constant current of 0.1C (about 30mA / g). The value obtained by dividing the amount of electricity supplied by the load of the hard carbon material on the electrode was the charge capacity of the hard carbon (mAh / g). The capacity at this time was defined as the gram capacity of the hard carbon material (mAh / g), and the percentage of the charge capacity to the discharge capacity was called the first coulomb efficiency (%). For the experimental batteries made from the same batch of samples, 6 groups of half-cells were tested under the same environmental conditions. The 6 gram capacities and first coulombic efficiencies were obtained. After removing the lowest and highest values, the average of the remaining 4 groups was taken as the gram capacity and first coulombic efficiency of the batch of samples.

[0256] The experimental parameters and effect data of each embodiment and comparative example are listed in the following Table 2.

[0257]

[0258] As can be seen from Table 2 above, the biochar preparation method of the present application controls the concentration temperature at 30-220°C and the carbonization temperature at 80-800°C. The performance of the water-coal slurry prepared using the prepared biochar is relatively excellent, with a high slurry concentration and a low apparent viscosity; the electrochemical performance of the battery prepared using the prepared biochar is relatively excellent, and the battery gram capacity and the first coulomb efficiency are both high. The performance of the water-coal slurry and battery prepared from the biochar of Examples 1 to 19 of the present application is better than that of Comparative Example 1.

[0259] Further, it can be seen from Examples 3 to 7 or Examples 9 to 13 that when the concentration temperature is in the range of 70 to 130° C., the obtained water-coal slurry has the best performance, high slurry concentration and low apparent viscosity; it can also be seen from Examples 3 to 7 or Examples 9 to 13 that when the concentration temperature is in the range of 70 to 140° C., the obtained battery has the best electrochemical performance, and the battery gram capacity and first coulomb efficiency are high;

[0260] According to Examples 9, 14 to 17 and 19, it can be seen that when the carbonization temperature is in the range of 110 to 500°C, the performance of the water-coal slurry obtained is relatively better, with high slurry concentration and low apparent viscosity; when the carbonization temperature is in the range of 130 to 160°C, the performance of the water-coal slurry obtained is optimal; according to Examples 9, 14 to 17 and 19, it can also be seen that when the carbonization temperature is in the range of 110 to 500°C, the electrochemical properties of the obtained battery are relatively better, and the battery gram capacity and first coulombic efficiency are relatively higher; when the carbonization temperature is in the range of 130 to 500°C, the electrochemical performance of the obtained battery is optimal, and the battery gram capacity and first coulombic efficiency are the highest.

[0261] The above is only the preferred embodiment of the present application, and does not limit the present application in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present application without departing from the technical solution of the present application still falls within the protection scope of the technical solution of the present application.

Claims

1. Application of a carbon material in preparing a battery, wherein: The carbon material is prepared by pre-carbonizing, gas-phase deashing and calcining biomass charcoal; The biochar is prepared by the following method: Concentrating the cooking liquid to obtain solids, wherein the solids contain lignin, inorganic salts, hemicellulose and cellulose; Carbonizing the solid matter, washing with a solvent and filtering the solid matter after carbonization to obtain biochar; Wherein, the solvent is an acid solution; the concentration temperature is 70-130°C; the carbonization temperature is 100-350°C; Based on the total weight of the biochar, the biochar comprises: 20-89 wt % of fixed carbon, 10-70 wt % of volatile matter, and 0.1-5 wt % of ash; The cooking liquid is the liquid part obtained by cooking plant straw, bamboo and wood with an organic solvent and then performing solid-liquid separation, and comprises: an organic solvent, lignin, an inorganic salt, hemicellulose and cellulose.

2. The use according to claim 1, wherein: The carbon material is a battery hard carbon material.

3. The use according to claim 2, wherein: The battery hard carbon material is a sodium ion battery hard carbon material.

4. The use according to claim 2, wherein: The battery hard carbon material is a battery hard carbon negative electrode material.

5. The use according to claim 1, wherein: The washing temperature is 0~100℃ and the washing time is 0.1~120min.

6. The use according to claim 5, wherein: The washing temperature is 60~80℃.

7. The use according to claim 5, wherein: The washing time is 30~60min.

8. The use according to any one of claims 1 to 7, wherein The concentration time is 0.1~6h.

9. The use according to any one of claims 1 to 7, wherein Based on the total weight of the solids, the solids contain: 5-91 wt % of lignin, 1-10 wt % of inorganic salts, and 1-50 wt % of hemicellulose and cellulose.

10. The use according to any one of claims 1 to 7, wherein: The carbonization time is 0.1~10h.

11. The use according to any one of claims 1 to 7, wherein: The carbonization time is 0.5~5h.

12. A method for preparing biochar, wherein: The following steps are involved: Concentrating the cooking liquid to obtain solids, wherein the solids contain lignin, inorganic salts, hemicellulose and cellulose; Carbonizing the solid matter, washing with a solvent and filtering the solid matter after carbonization to obtain biochar; Wherein, the solvent is an acid solution; the concentration temperature is 70-130°C; the carbonization temperature is 100-350°C; Based on the total weight of the biochar, the biochar comprises: 20-89 wt % of fixed carbon, 10-70 wt % of volatile matter, and 0.1-5 wt % of ash; The cooking liquid is the liquid part obtained by cooking plant straw, bamboo and wood with an organic solvent and then performing solid-liquid separation, and comprises: an organic solvent, lignin, an inorganic salt, hemicellulose and cellulose.

13. The method according to claim 12, wherein: The washing temperature is 0~100℃ and the washing time is 0.1~120min.

14. The method according to claim 13, wherein: The washing temperature is 60~80℃.

15. The method according to claim 13, wherein: The washing time is 30~60min.

16. The method according to any one of claims 12 to 15, wherein The concentration time is 0.1~6h.

17. The method according to any one of claims 12 to 15, wherein Based on the total weight of the solids, the solids contain: 5-91 wt % of lignin, 1-10 wt % of inorganic salts, and 1-50 wt % of hemicellulose and cellulose.

18. The method according to any one of claims 12 to 15, wherein: The carbonization time is 0.1~10h.

19. The method according to any one of claims 12 to 15, wherein the carbonization time is 0.5 to 5 h.

20. The method according to any one of claims 12 to 15, wherein The biochar contains 30-70 wt % of fixed carbon.

21. The method according to any one of claims 12 to 15, wherein: Based on the total weight of the ash, the ash contains: at least 50 wt % of metal elements, at most 10 wt % of silicon elements, at most 20 wt % of phosphorus elements, and at most 20 wt % of sulfur elements.

22. The method according to claim 21, wherein: The ash contains at least 30 wt % of potassium, based on the total weight of the ash.

23. A biochar prepared by the method according to any one of claims 12 to 22, wherein: Based on the total weight of the biochar, the biochar comprises: 30-70 wt % of fixed carbon, 10-70 wt % of volatile matter, and 0.1-5 wt % of ash; Based on the total weight of the ash, the ash contains: at least 50 wt% of metal elements, at most 10 wt% of silicon elements, at most 20 wt% of phosphorus elements, and at most 20 wt% of sulfur elements; The ash contains at least 30 wt % of potassium, based on the total weight of the ash.

24. The biochar according to claim 23, wherein: Its calorific value is not less than 4500kcal / kg.

25. Use of biochar prepared by the method according to any one of claims 12 to 22 in fuel, gasification raw material for gasifiers, and battery carbon materials.

26. The use according to claim 25, wherein: The biomass charcoal is directly used as a fuel or a raw material for gasification of a gasifier; or, the biomass charcoal is crushed and made into a biomass slurry by adding water and a dispersant, and then used as a fuel or a raw material for gasification of a gasifier.

27. The use according to claim 26, wherein: The biomass charcoal is used as a battery carbon material after being pre-carbonized, gas-phase deashed and calcined.

28. The use according to claim 25, wherein: The battery carbon material is a battery hard carbon material.

29. The use according to claim 28, wherein: The battery hard carbon material is a sodium ion battery hard carbon material.

30. The use according to claim 28, wherein: The battery hard carbon material is a battery hard carbon negative electrode material.

Citation Information

Patent Citations

  • Carbon negative electrode material of sodium ion battery

    CN102701184A

  • Technologies for extracting cellulose from biomass raw material and preparing biochar

    CN103103845A

  • Biomass hard carbon negative electrode material for sodium ion battery as well as preparation method and application of biomass hard carbon negative electrode material

    CN113381016A